Molecular detection and differentiation of Brazilian and African isolates of the entomopathogen Neozygites tanajoae (Entomophthorales: Neozygitaceae) with PCR using specific primers - Agboton, B.V.; Junior, I.D.; Hanna, R.; Tiedemann, A. von (Informa UK Limited, 2009)
Neozygites tanajoaeis an entomopathogenic fungus which has been used forbiocontrol of the cassava green mite (Mononychellus tanajoa, CGM) in Africa.Establishment and dispersal of Brazilian isolates which have been introduced intosome African countries in recent years to improve CGM control was followedwith specific PCR assays. Two primer pairs, NEOSSU_F/NEOSSU_R and8DDC_F/8DDC_R, were used to differentiate isolates collected from severallocations in Brazil and from three countries in Africa, Benin, Ghana andTanzania. The first primer pair enabled the species-specific detection ofNeozygites tanajoae, while the second differentiated the Brazilian isolates fromthose of other geographical origin. PCR assays were designed for detection offungal DNA in the matrix of dead infested mites sinceN. tanajoaeis difficult toisolate and culture on selective artificial media. Our results show that all isolates(Brazilian and African) that sporulated on mummified mites were amplified withthe first primer pair confirming theirNeozygites tanajoaeidentity. The secondpair amplified DNA from all the Brazilian isolates, but did not amplify any DNAsamples from the African isolates. None of the two primers showed amplificationneither from any of the non-sporulating mite extracts nor from the deaduninfected mites used as negative controls. We confirmed that the two primerpairs tested are suitable for the detection and differential identification ofN.tanajoaeisolates from Brazil and Africa and that they are useful to monitor theestablishment and spread of the Brazilian isolates ofN. tanajoaeintroduced intoBenin or into other African countries for improvement of CGM biocontrol.